Aid and the environment: Uganda - Eseza Kateregga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper seeks to (i) establish the areas in which aid from the major donors is concentrated; (ii) examine how aid has been allocated to the environmental sectors, and (iii) review the factors behind the success of environmental projects. Using data from the Aiddata.org database, the distribution of environment-related aid, commitments and disbursements from the major donors over the period 2005 - 11 is examined. Recipients of aid and donors were interviewed to learn their perceptions on aid flows and the success of environmental projects. The analysis shows that although many of the key donors commit aid to environmental sectors, there was considerable non-disbursement by both multilateral and bilateral donors; a small percentage of aid from multilateral donors was geared towards the environment. Strong involvement of local communities in projects is a key to the success of environmental projects.
Keywords: O2; Q3; Q56; 330; development plan; environmental aid; aid commitments; aid disbursements